P-101 Implementing the therapy outcome measure (TOM) in a day hospice. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Boa, Sally; Foster, Gill; Malcomson, Mandy
Abstract : Background: Hospice Day Services provide support to people to enable them to live with life limiting illness. The focus is on enhancing well-being and supporting people to continue to participate in activities that are important to them. Commonly used palliative care outcome measures tend to focus on problems and symptoms rather than well-being, activity and participation. The Therapy Outcome Measure (TOM) has been developed using the World Health Organization's International Classification of Functioning, Disability and Health and allows professionals to rate the person against descriptors which relate to four different domains: Impairment, Activity, Participation and Well-being. Aim: We aimed to find out if the TOM Palliative Care Scale could be used reliably and on a routine basis in Day Hospice by the multidisciplinary team to measure the impact of their interventions. Methods: Staff working in Day Hospice received training to become familiar with the TOM scales and use the scales reliably. TOM was used with every patient referred to Day Hospice at two points during their episode of care; within the first two weeks and 12 weeks later. Patients were also assessed using the Australian Karnofsky Performance Status (AKPS), which provided information about functional status. Findings: Over a 22 week period, initial TOMs were used with 70 patients. Thirteen patients had TOM scores at 1 and 12 weeks as many patients deteriorated or stopped attending before the 12 week review. Changes in TOMs scores at these time points showed improvements in patients' well-being, activity and participation whilst impairment stayed the same. No changes were seen in AKPS level for this group. Conclusions: TOM scoring was readily adopted by those who received training. It was relatively quick to complete and provided meaningful information that reflected the impact of the interventions. Reducing the length of time between scores may enable collection of comparative scores for more patients.